Curriculum of the course of Pedagogy: A Reflection on the teacher and in Teaching Mathematics in Elementary School - Ribeiro, José Augusto; Albrecht, Evonir (Research, Society and Development, 2018)
The present article proposes a reflection on the curriculum of the Pedagogy course and the teacher who will act in the Teaching of Mathematics, in the initial years of Elementary School. It is observed that the Pedagogy courses offered promote the development of pedagogical skills, especially in the field of Didactics, on entering, it is verified that there is a possible deficiency in the basic training of these future teachers, so it is proposed to reflect on, as the Curriculum of the course of Pedagogy can contribute to reduce the impact between two realities: the one experienced in the course of Pedagogy and the teaching praxis in its classroom? In order to better understand this complex scenario, three higher education institutions were selected in the region of Grande ABC, in São Paulo, and the curricular components that comprise Mathematics Education were analyzed, in a qualitative perspective, from the perspective of documentary analysis. The proposed reflection reveals the importance of having a more holistic view about the basic education of the student entering the Pedagogy course, in order to understand the real needs and, in this way, to provide a training that can contribute to improvement in the teaching process of Mathematics in Elementary School.